Protection from chronic stress- and depressive symptom-induced vascular endothelial dysfunction in female rats is abolished by preexisting metabolic disease - Brooks, Steven D. (Am J Physiol Heart Circ Physiol, 2018)
While it is known that chronic stress and clinical depression are powerful predictors of poor cardiovascular outcomes, recent clinical evidence has identified correlations between the development of metabolic disease and depressive symptoms, creating a combined condition of severely elevated cardiovascular disease risk. In this study, we used the obese Zucker rat (OZRs) and the unpredictable chronic mild stress (UCMS) model to determine the impact of preexisting metabolic disease on the relationship between chronic stress/depressive symptoms and vascular function. Additionally, we determined the impact of metabolic syndrome on sex-based protection from chronic stress/depressive effects on vascular function in female lean Zucker rats (LZRs). In general, vasodilator reactivity was attenuated under control conditions in OZRs compared with LZRs. Although still impaired, conduit arterial and resistance arteriolar dilator reactivity under control conditions in female OZRs was superior to that in male or ovariectomized (OVX) female OZRs, largely because of better maintenance of vascular nitric oxide and prostacyclin levels. However, imposition of metabolic syndrome in combination with UCMS in OZRs further impaired dilator reactivity in both vessel subtypes to a similarly severe extent and abolished any protective effect in female rats compared with male or OVX female rats. The loss of vascular protection in female OZRs with UCMS was reflected in vasodilator metabolite levels, which closely matched those in male and OVX female OZRs subjected to UCMS. These results suggest that presentation of metabolic disease in combination with depressive symptoms can overwhelm the vasoprotection identified in female rats and, thereby, may reflect a severe impairment to normal endothelial function. NEW & NOTEWORTHY This study addresses the protection from chronic stress- and depression-induced vascular dysfunction identified in female compared with male or ovariectomized female rats. We determined the impact of preexisting metabolic disease, a frequent comorbidity of clinical depression in humans, on that vascular protection. With preexisting metabolic syndrome, female rats lost all protection from chronic stress/depressive symptoms and became phenotypically similar to male and ovariectomized female rats, with comparably poor vasoactive dilator metabolite profiles.